2003
DOI: 10.1016/s0006-3495(03)70048-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy Trapping and Detrapping in Reaction Center Mutants from Rhodobacter sphaeroides

Abstract: Time-resolved fluorescence of chromatophores isolated from strains of Rhodobacter sphaeroides containing light harvesting complex I (LHI) and reaction center (RC) (no light harvesting complex II) was measured at several temperatures between 295 K and 10 K. Measurements were performed to investigate energy trapping from LHI to the RC in RC mutants that have a P/P(+) midpoint potential either above or below wild-type (WT). Six different strains were investigated: WT + LHI, four mutants with altered RC P/P(+) mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
(81 reference statements)
2
18
0
Order By: Relevance
“…Interestingly, approximately the same transfer times as in PSII are found between the LH1 core antenna and the RC in purple bacteria (upper part of Fig. 1, Bergström et al (1989); Visscher et al (1989); Sundström et al (1999); Katiliene et al (2003)) despite the different organization of the antenna. A common property of both photosystems, which is responsible for this behavior, is the relatively large distance between the pigments in the RC and those in the antennae.…”
Section: Purple Bacteriasupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, approximately the same transfer times as in PSII are found between the LH1 core antenna and the RC in purple bacteria (upper part of Fig. 1, Bergström et al (1989); Visscher et al (1989); Sundström et al (1999); Katiliene et al (2003)) despite the different organization of the antenna. A common property of both photosystems, which is responsible for this behavior, is the relatively large distance between the pigments in the RC and those in the antennae.…”
Section: Purple Bacteriasupporting
confidence: 52%
“…Transmembrane helices (red and yellow cylinders) are depicted together with the macrocycles of bacteriochlorophyll a pigments (green). The energy levels of excited states of LH1 and RC and the transfer times between them, as obtained from an analysis of time-resolved spectra by Katiliene et al (2003) are shown below the structure. kT denotes the thermal energy at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the third component was small in amplitude but required to obtain a better fitting to the decay profile 27 and was assigned to relaxation of the nearequilibrium mixture of excited and charge-separated states. 31 A recent study of Stark absorption spectroscopy 9 indicated that relatively large changes in the dipole moment and polarizability in Tch. tepidum arise from mixing of a charge transfer state into the lowest exciton state of the special pair 40 and LH1 41 as a result of closely packed and excitonically coupled BChl a molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Also, the rates of fast ET steps can be very sensitive to protein dynamics and conformation (28,49,50). Such protein relaxation is well known for bacterial RCs (27,29,49,51,52) and isolated PSII RCs (37)(38)(39)(53)(54)(55). Protein dynamic processes span a huge range of time, from picoseconds to hours (32,(56)(57)(58).…”
Section: Protein Dynamicsmentioning
confidence: 99%